Could Physical Activity Have any Role in Cardiovascular Disease Prevention in Prisoners? A Systematic Review. - Papa, Veronica; Tafuri, Domenico; Vaccarezza, Mauro (2021)
More than 10.74 million people are currently held in penal institutions worldwide. Moreover, there is also evidence that the percentage of elder and female prisoners has been consistently growing. Cardiovascular diseases are the leading cause of death worldwide. Exercise training and physical activity help to prevent both primary and secondary cardiovascular events. Data on the influence of physical activity on the well-being in prison population is scarce. Here, we discussed, in a systematic review, the general health conditions and the cardiovascular risk profile in the prisoners compared to the general population and evaluated whether or not exercise could be a valuable tool in preventing these diseases in inmates. We performed a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement: 769 were initially identified, and a total of 24 studies were finally included. Nine studies evaluated the health conditions in prisoners, five studies evaluated the incidence of cardiovascular disease (CVD) and coronary heart disease (CHD) in the prison population, and 10 studies evaluated the feasibility and the effectiveness of exercise programs in prisoners. Sports-educational programs can benefit prison inmates. It appears that supervised exercise training is an effective coping strategy to deal with incarceration. Moreover, it seems the sports programs might be a useful tool in improving physical and mental health of prisoners as well as in decreasing cardiovascular risk factors.